Organizational Information Integration and Team Performance: An Inter and Intra Organizational Perspective - Wajeeha Hasnain; Dr. Urooj Pasha (Journal of Management Practices, Humanities and Social Sciences, 2022)
As construction teams are comprised of multi skilled individuals with varying experiences that are required to work on different projects throughout their career. This research seeks to reconnoiter the role of Information integration in Performance of construction Teams. The United Arab Emirates is protuberant country for construction activities because of considerable investments in mega projects and distinguishing architectural designs. Therefore, survey research is conducted in the United Arab Emirates to understand the relationship of inter-organization information integration and intra-organization information integration of the contracting firms with team performance. The data obtained is then technically analyzed through Structural Equation Modelling (SEM). Results indicates that Inter organization information integration and intra organization information integration have impacts on construction team performance. Based on findings, a model is presented to help improve team performance by understanding the significant role of information integration.The momentous research aid the relation of inter organization information integration and intra organization information integration with team performance thus providing a foundation for new research that can build and strengthen the varying dynamics of Information Integration.Information integration has vivacious standing in expediting operations of construction projects, explicitly improving construction team performance. However, the dynamic nature of the construction industry projects makes it an area of immense need of exploration. The contracting firms that usually work on more than one project can yield better results by improving team performance. Thus, result in improved Firm’s performance.